Concept of Citizenship Amendment Bill- 2019 (International Journal of Food and Nutritional Sciences, 2021)
In this article author critically analyze the citizenship amendment bill, 2019, citizen is legal relation between a people with the state The Citizenship (Amendment) Bill is seen in Assam as against the letters and spirit of Clause 6 of the Assam Accord. The local population from the state and other parts of northeast India feel that, with this bill coming into effect, the region will be flooded with a large number of immigrants, which will dilute their culture and identity. On the other hand, the Union government of India argues that the persecuted religious minorities from the neighbouring countries have nowhere to go except India. It has also been clarified that those people can go to any state of India, and not only to Assam. However, given the history of immigration and tensions due to it, a section of Assamese and people from the neighbouring states are not convinced by this argument. This bill is also against the basis structure of the constitution that is Secularism. One organization from Assam has filed writ petition against this bill in Supreme Court as it is unconstitutional. This particular bill is also against the ASSAM ACCORD, 1985, and even inside the government some members and the allies parties of government are against this bill. The author analyzed the social condition of Assam and the consequences of this bill over the state of Assam. February 2020 Special Issue 038 The citizenship Amendment bill, 2019 tries to amend the existing The Citizenship Act, by including provisos in Sec 2(1) (b) and in clause (d) of third schedule. This amendment bill caused disturbance and violence in northeast region especially in the State of Assam.